Minimally invasive techniques in thymic surgery: a worldwide perspective - BATIREL, HASAN FEVZİ (My University, 2018)
Minimally invasive surgical techniques are important in surgical management of thymic pathologies. Traditional access techniques are being replaced with minimally invasive techniques using multiportal or uniportal approach. Adoption of minimally invasive techniques for thymic malignancies has been slow due to long term recurrence concerns. Recent studies show that minimally invasive video-assisted thoracoscopic surgery (VATS) or robotic approach to early stage thymic malignancies are associated with less intraoperative bleeding, lower rate of respiratory complications, shorter chest tube duration and shorter hospital stay. Oncologic outcomes are at least equivalent to open approach. Minimally invasive approach for benign pathologies is widely applied. There are significant variations in VATS approaches for thymus, showing a multinational interest in the issue of minimizing trauma during thymectomy. Use of robotic technology is also popular, as the retrosternal area is a narrow anatomic space to manipulate conventional instruments. The evolution of minimally invasive surgery for thymus has been possible with contribution from centers all around the world. In the current practice, various approaches are being adopted and every surgeon should prefer a technique depending on surgical preference and experience.
Keywords: subxiphoid; thymectomy; thymomectomy; Video-assisted thoracoscopic surgery (VATS)